1994
DOI: 10.1007/bf00203143
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures of AIPO4 subjected to high shock pressures

Abstract: Abstract. Berlinite single crystal specimens were shocked to peak pressures 12 and 24 GPa. Specimens were placed in an AI capsule to minimize shock-wave reflections at interfaces between specimen and capsule. Shock pressures were achieved with a 6.5-m-long two-stage gun. The shock-induced microstructures in recovered specimens were then investigated by Transmission Electron Microscopy. In the sample shocked at 12 GPa, the prominent shock-induced defects are dislocations and basal a glide appears to be the only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…These authors also found that the high pressure phase (>15 GPa) was not elastically isotropic and instead was an anisotropic glass. Observations of amorphous phase from the samples after non-hydrostatic compression in the ungasketted diamond anvil cell [6] as well as in the recovered samples after shock loading [7] further supported the idea of the high pressure phase being the amorphous phase.…”
Section: Introductionmentioning
confidence: 64%
“…These authors also found that the high pressure phase (>15 GPa) was not elastically isotropic and instead was an anisotropic glass. Observations of amorphous phase from the samples after non-hydrostatic compression in the ungasketted diamond anvil cell [6] as well as in the recovered samples after shock loading [7] further supported the idea of the high pressure phase being the amorphous phase.…”
Section: Introductionmentioning
confidence: 64%
“…And if shock loading and/or non-hydrostatic stress loading of the α-phase leads to a Cmcm phase then our simulations suggest that on recovery one may observe the glassy phase (as experimentally found! [4]) which arises from the Cmcm phase. In the light of results of section 3.2.2, this amorphous phase will not be the same as the high pressure disordered phase.…”
Section: 23mentioning
confidence: 99%
“…Berlinite AlPO 4 exists in the α-quartz structure at ambient conditions and like quartz, it is reported to become amorphous at high pressures [1][2][3][4][5][6][7]. However, in AlPO 4 , this transformation is reversible and the high pressure amorphous phase has been termed as a memory glass [1], as on the release of pressure the amorphous phase transforms back to the single crystal with the same orientations.…”
Section: Introductionmentioning
confidence: 99%
“…martensitic transformations and crystal to amorphous phase transitions have also been studied. [11][12][13][14][15][16][17][18][19][20][21] Solid state structural phase transformations from low to high or from high to low density states have been considered to occur via reconstructive or displacive mechanisms. 22 Such displacive phase transformations involve coordinated shifts of atoms comprising of homogeneous strain and shuffle, and hence, are favoured under high pressure, while reconstructive transformations are less likely to occur at high pressures due to the reduced mobility of atoms.…”
Section: Introductionmentioning
confidence: 99%